Inequalities in health system coverage and quality: a cross-sectional survey of four Latin American countries - Javier Roberti, PhD; Hannah H Leslie, PhD; Svetlana V Doubova, PhD; Jesús Medina Ranilla, MD; Agustina Mazzoni, MSc; Laura Espinoza, BS; Renzo Calderón, MSc; Catherine Arsenault, PhD; Ezequiel García-Elorrio, PhD; Patricia J García, ProfPhD (Elsevier, 2024)
Summary: The premise of health as a human right in Latin America has been challenged by health system fragmentation, quality gaps, a growing burden of chronic disease, sociopolitical upheaval, and the COVID-19 pandemic. We characterised inequities in health system quality in Colombia, Mexico, Peru, and Uruguay. We did a cross-sectional telephone survey with up to 1250 adults in each country. We created binary outcomes in coverage, user experience, system competence, and confidence in the system and calculated the slope index of inequality by income and education. Although access to care was high, only a third of respondents reported having a high-quality source of care and 25% of those with mental health needs had those needs met. Two-thirds of adults were able to access relevant preventive care and 42% of older adults were screened for cardiovascular disease. Telehealth access, communication and autonomy in most recent visit, reasonable waiting times, and receiving preventive health checks showed inequalities favouring people with a high income. In Uruguay, inequality between government and social security services explained a substantial proportion of disparities in preventive health access. In other study countries, inequalities were also substantial within government and social security subsectors. Essential health system functions are unequal in these four Latin American countries.